Hydrodynamic study of the Single-Stirred Membrane Filtration Module: A CFD-based approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Membrane based separation technologies are nowadays very often recommended over the traditional separation techniques because of their simple modular design, low power consumption, easy way handling, and hazard-free operation. A large number of membrane modules were proposed over time to suit for the specific operational requirement. For instance, the Dynamic Shear Enhanced membrane filtration units, which include Rotating Disk, Rotating Disk-Membrane, Vibratory Shear Enhanced Processing units, Multi-Shaft Disk, and many others, were introduced to generate feed flow independent high shear rate at the membrane surface to effectively alleviate the problems of concentration polarization and membrane fouling. The single-stirred cell, alternativelyknown as rotating disk device, is recognized as one of the baseline DSE modules. The design is pretty simple. The module is a dead-end unit with a flat disk stirrer placed close to the membrane surface. Imperatively, many experimental studies have been reported on the performance of the Dynamic Shear Enhanced filtration devices. Nevertheless, reports on the corresponding hydrodynamic analysis are quite rare. The present work demonstrates the fundamental hydrodynamic characteristics, such as the velocity field and the shear stress distribution, of a single-stirred cell using CFD. The k-ε realizable turbulent model was chosen to simulate this module. Analysis was based on the variation of transmembrane pressure and rotational velocity.